Safety and immunogenicity of the COVID-19 vaccine BNT162b2 for patients with breast and gynecological cancer on active anticancer therapy: Results of a prospective observational study - De Placido, Pietro; Pietroluongo, Erica; De Angelis, Carmine; Tafuro, Margherita; Barraco, Chiara; Giannatiempo, Rosa; Buonaiuto, Roberto; Schettini, Francesco; Iervolino, Anna; Vozzella, Emilia Anna; Giuliano, Mario; Bianco, Roberto; et al. (Frontiers in Oncology, 2022)
Background: Vaccines against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) are highly effective. Nevertheless, immunocompromised participants were excluded from randomized controlled clinical trials. This study evaluates the efficacy and safety of the Pfizer/BioNtech BNT162b2 (BNT162b2) vaccine in patients with breast and gynecological cancer treated with active anti-cancer therapy versus a control cohort of healthy participants. Methods: Immune responses to the BNT162b2 vaccine in patients with breast cancer (n=44) or a gynecological malignancy (n=6) on active anti-cancer therapy (28 on chemotherapy, mostly anthracycline- or taxane-based and 22 on target therapy), and in a control cohort of participants without cancer (n=67) were investigated by SARS-CoV-2 neutralizing antibody titers measured by S1-binding immunoglobulin G (IgG) concentrations assessed using the LIAISON XL tools (DiaSorin SpA). Response was assessed after a second dose of the BNT162b2 vaccine administered before and at least 3 weeks after the vaccine dose. Results: Overall, 43/50 (86%) patients of the cancer cohort (74% in the breast cancer group and 100% in the gynecological malignancy group), developed IgG antibodies after the second dose of the BNT162b2 vaccine. There were no statistically significant differences in responder rates between patients treated with chemotherapy and those on target therapy. The majority of patients who received chemotherapy with or without target therapy, 21/28 (75%), developed a reliable antibody titer after vaccine. All 7 non-responder patients were undergoing an anthracycline-based regimen. Based on IgG levels (0 - 400 AU/ml), patients were classified negative (“non-responders”), weakly-positive or strongly-positive (“responders”). No delay in cancer therapy schedule or reported side effect were recorded after BNT162b2 vaccine administration. All healthy participants were strongly-positive. Responder rates differed significantly between the two study cohorts (p<0.001). Conclusions: Most patients develop antibody titers after the second immunization. However, given the persistence of non-weakly responders, additional immunization booster seems to be required, along with a proactive planning in vaccination schedule, with vaccine administration spaced out over time with respect to chemotherapy.